Single-Stage versus Three-Stage Repair in Anorectal Malformations with Rectovestibular Fistula: A Prospective Observational Study - Pandya, Kashyap; Patolia, Rajesh; Pandya, Ananyaa; Mohammed, Bemat Gulamhusen (Journal of Neonatal Surgery, 2025)
Background: Rectovestibular fistula is the most common subtype of anorectal malformation in females. While the traditional three-stage repair remains the standard in many settings, single-stage repair is increasingly considered as a viable alternative in selected patients. Objective: To compare the short-term complications, long-term functional outcomes, and hospital stay between single-stage and three-stage repair in female patients with rectovestibular fistula. Methods: This prospective observational study included 30 female patients treated at KGP Children Hospital, Vadodara, between January 2015 and December 2024. Ten patients underwent single-stage repair, while twenty underwent traditional three-stage repair. Outcomes assessed included postoperative complications (wound infection, anal stenosis, perineal excoriation), fecal continence, constipation, and total hospital stay. Statistical comparisons were made using chi-square and t-tests. Results: Wound infection was more frequent in the single-stage group (40%) than in the three-stage group (5%). Good fecal continence was achieved in 70% of single-stage patients versus 55% in the three-stage group. Severe constipation was more prevalent in the three-stage group (35%). Mean hospital stay was significantly shorter in the single-stage group (4.8 ± 1.03 days) compared to the three-stage group (11.85 ± 1.81 days, p< 0.001). Conclusion: Single-stage repair for rectovestibular fistula offers comparable functional outcomes to the three-stage approach and significantly reduces hospitalization time. With proper case selection, it may be a safe and cost-effective alternative in resource-limited settings.